Pré-tratamento biológico da água residuária de lavagem do biodiesel de óleo de soja por micro-organismos produtores de lipase. - Rocha, Dayane Cristina da (2010)
Biodiesel is a derived fuel from renewable biomass that can substitute partially or totally the fossil fuel. The production process of the biodiesel is composed by the following stages: raw material preparation, transesterification reaction, phases separation, alcohol recovery and dehydration, glycerin destillation and purification of the renewable fuel, resulting in glycerin as a by-product and purification wastewater. The formed wastewater during the stage of purification presents high concentration of oils and greases, presenting potential to contaminate bodies of water. One of the treatment proposals of this residue is the enzymatic hydrolysis use by lipases for removal of oils and greases. Due the specificity of lipases and its large technological application, it appears that it is necessary to search new microorganisms producers of this enzyme, with specific characteristics to the residue in study. Therefore, its objective was to evaluate the biodegradation of the biodiesel washing(purification) water, gotten trough transesterification between soy oil and methanol, by means of production of lipase, using isolated microorganisms from the proper residue. For both, analyses of the initial physicist-chemistries characteristics had been made with the residuary water of the biodiesel washing, then it had been isolated and chosen, by means of determinations of the lipase activity. Following, it was made a test of fat biodegradation, fixing the variables pH (5,95), temperature (35ºC), rotation (180 rpm) and nitrogen concentration (3 g.L-1) and establishing as variable the two microorganism preselected and the time (24, 48, 72, 96 and 120 h). At the time (48 h) and Klebsiella oxytoca microorganism defined, the optimization process of the fat removal in the treatment of the wastewater was initialized. For such, it was used a designed central composite (DCCR), establishing as independent variables pH and nitrogen concentration, the other variable ones had been previously fixed in: temperature 35ºC, rotation 180 rpm and 48 hours. For experimental validation of the model considered for fat removal it was carried through, in triplicate copy, a biodegradation test in the excellent established conditions. These results, on the other hand, had been compared to a kinetics one carried through the same conditions, but using as inoculun the commercial product Hábil FTW SF. The biodiesel purification wastewater had presented high potential of environmental impact, presenting a concentration of O&G of 6,76 g.L-1. From the six isolated microbiological cultures in the decantation tank of this effluent one, two microorganisms (A and B) had been selected presenting one high potential of lipase production, with enzymatic index of 0,56 and 0,57, respectively. Trough DCCR ways it has been concluded that the best point to the maximum efficiency of removal of O&G from the residuary water of biodiesel purification was equivalents to pH 7,5 and 4,00 g.L-1 of nitrogen, resulting in an efficiency of 60% in the removal of fat. The treatment of the wastewater using the proper isolated microorganism from the effluent (Klebsiella oxytoca) was not differentiated from the carried through essays using the commercial product Hábil FTW SF.